Da'wah Message of Social Stratification in George Orwell's Novel Nineteen Eighty-four (1984) - Nurholis, Nurholis (Ilmu Dakwah: Academic Journal for Homiletic Studies, 2022)
The research treats the novel as a unity of thought in which the elements are inter-related each other. The objectives of this paper are: identify a novel, through its messages, is potential to persuade and shape public mindset. One of the outstanding novels is Nineteen Eighty-four (1984), it contains of so much religious endeavors. As a result, this study is conducted to find out the presentation of religious endeavors through social criticism, ethic, moral, behavioral values in the novel. Booker and Barry are used in analysing the novel, and Eagleton is used in understanding of Marxist Literary Criticism. Methods and data collection techniques used are descriptive qualitative. The result is the differences between social classes that cause power struggles have relation of theme. That is the characterization of bourgeois and proletarian in this novel comes up early in the social condition, and it is capable for illustrating the social reality at that time. In the novel, the strongest and weakest appears clearly. The characterization describes how their working conditions, their place, and their live is and how he went down to sees the working conditions down there. The characters and actions in the novel are imaginary in nature, in other words they seem to ‘representative of real life’ which are different, strange, and irrational. Thus, the different between the production and the employment, the owner and the worker, the strongest and the weakest, are subordinate that places as a subject and as an object.